Is it all about awareness? The normalization of coastal risk - Luís, S.; Pinho, L.; Lima, M. L.; Roseta-Palma, C.; Martins, F. C.; Almeida, A. B. (Journal of Risk Research, 2016)
Coastal risk is already high in several parts of the world and is expected to be amplified by climate change, which makes it necessary to outline effective risk management strategies. Risk managers assume that increasing awareness of coastal risk is the key to public support and endorsement of risk management strategies – an assumption that underlies a common worldview on the public understanding of science, which has been named the deficit model. We argue that the effects of awareness are not as straightforward. In particular, awareness of coastal hazards might not lead to more technically accurate risk perceptions. Based on research on risk perception normalization, we explored the hypothesis that coastal risk awareness reduces coastal risk perception – in particular the perceived likelihood of occurrence of coastal hazards – through its effect on reliance on protective measures to prevent risk. Individuals can rely on protective measures, even when those are not effective, as a positive illusion to reduce risk perception. This effect might be stronger for higher probability hazards and for permanent residents of costal zones. Data from 410 individuals living in coastal zones corroborated most of our expectations. Global results demonstrated a risk normalization effect mediated by reliance on current measures. Additional analyses made clear that this effect occurred in 2 of the 5 high-probability hazards (flood and storm), and not in the low-probability hazard (tsunami). Normalization might be more likely among high-probability hazards which entail catastrophic and immediate impacts. This effect was also found among permanent residents, but not among temporary residents. Results imply that coastal risk management might benefit from (a) taking risk perception normalization effects into account, (b) tailoring strategies for permanent and temporary residents and (c) promoting a higher public engagement, which would facilitate a more adaptive and effective coping with coastal risk than the use of positive illusions.